2019
DOI: 10.1029/2019jb017983
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State for Shocked Fe‐8.6 wt% Si up to 240 GPa and 4,670 K

Abstract: Using dynamic compression technique, the equation of state for Fe‐8.6 wt% Si was measured up to 240 GPa and 4,670 K. A least squares fit to the experimental data yields the Hugoniot parameters C0 = 4.603±0.101 km/s and λ = 1.505±0.037 with initial density ρ0=7.386±0.021 g/cm3. Based on the Hugoniot data, the calculated isothermal equation of state is consistent with static compression data when the lattice Grüneisen parameter γl =1.65(7.578/ρ) and electronic Grüneisen parameter γe=1.83. The calculated pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
(158 reference statements)
1
18
1
Order By: Relevance
“…We should note that the concentration of Si in the core remains uncertain. While some experiments have shown that Fe alloyed with ∼9 wt % Si can satisfy the density profile of the outer core and Fe alloyed with ∼4 wt % Si for the inner core, respectively ( 37 , 40 , 41 , 51 , 52 ), other studies indicate that a dominant Si light alloying component is unable to reproduce both the density and sound velocity distribution in the outer core ( 53 , 54 ).…”
mentioning
confidence: 99%
“…We should note that the concentration of Si in the core remains uncertain. While some experiments have shown that Fe alloyed with ∼9 wt % Si can satisfy the density profile of the outer core and Fe alloyed with ∼4 wt % Si for the inner core, respectively ( 37 , 40 , 41 , 51 , 52 ), other studies indicate that a dominant Si light alloying component is unable to reproduce both the density and sound velocity distribution in the outer core ( 53 , 54 ).…”
mentioning
confidence: 99%
“…Davies (2015), Si is partitioned between solid and liquid Fe almost equally. Therefore, we assume that the inner core contains only Si and has the same amount of Si as the liquid core, in agreement with Huang et al (2019).…”
mentioning
confidence: 85%
“…Rocky planets are generally believed to have Fe-rich metallic cores containing minor contents of light elements, which may be S, O, Si, C, or H. However, there is still controversy over which light element(s) are dissolved in the Earth's core (e.g., Hirose et al, 2013). Hirose et al (2013) suggested that the liquid core contains approximately 6 wt% Si, 3 wt% O, and 1-2 wt% S. Huang et al (2019) provided evidence that the liquid core contains 5.6 ± 3.0 wt% S and 3.8 ± 2.9 wt% Si satisfying both geophysical and geochemical constraints. We assume that the light elements within the liquid core in our models are Si and S. We use three equation of state parameters, namely, ε-Fe (Fei et al, 2016), Fe-9Si (Huang et al, 2019), and Fe-12S (Huang et al, 2018), which were obtained from high-pressure experiments; the experiments are summarized in Table 2.…”
Section: Corementioning
confidence: 99%
See 2 more Smart Citations